Pengaruh Gaya Kepemimpinan Transformasional Kepala Sekolah dan Budaya Organisasi terhadap Kompetensi Guru Sekolah Dasar di Kabupaten Aceh Barat - Yusransal*, Yusransal; Marwan, Marwan; Syahrin, Alfi (Universitas Syiah Kuala, 2023)
The aims of this research are (1) To analyze the influence of the principal's transformational leadership style on the professional competence of teachers in State Elementary Schools in Meureubo District, West Aceh Regency, (2) To analyze the influence of organizational culture on the professional competence of teachers in State Elementary Schools in Meureubo District, Regency West Aceh, and (3) To analyze the influence of the principal's transformational leadership style and organizational culture on the professional competence of teachers in State Elementary Schools in Meureubo District, West Aceh Regency. This research uses quantitative methods with a descriptive approach, population of 101 people, 80 subjects, simple random sampling technique using the Slovin formula with a margin of error of 0.05%, Likert scale questionnaire data collection technique and multiple linear regression data processing technique. The research findings were partially obtained, (1) The principal's transformational leadership style had an effect on teacher competence by 0.607 or 60.7% and (2) Organizational Culture had an effect on teacher competence by 0.301 or 30.1%. Meanwhile, simultaneously it was found that the principal's transformational leadership style and organizational culture had an influence on teacher professional competence with a constant value of 9.986. The findings in this research have practical implications, namely that improving the transformational leadership style of school principals and organizational culture can result in increasing the professional competence of elementary school teachers in cluster II, Meureubo District, West Aceh Regency. Advice to all school principals that this transformational leadership style and organizational culture have been tested for suitability and the results show that this transformational leadership style and organizational culture are very relevant for implementation in schools, so that they can be taken into consideration in the process of formulating programs or policies, both in schools , school supervisor and West Aceh Education and Culture Service.